2011
DOI: 10.1021/nn202163v
|View full text |Cite
|
Sign up to set email alerts
|

Working Together: The Combined Application of a Magnetic Field and Penetratin for the Delivery of Magnetic Nanoparticles to Cells in 3D

Abstract: Nanoparticles (NPs) are currently being developed as vehicles for in vivo drug delivery. Two of the biggest barriers facing this therapy are the site-specific targeting and consequent cellular uptake of drug-loaded NPs(1). In vitro studies in 2D cell cultures have shown that an external magnetic field (MF) and functionalization with cell-penetrating peptides (CPPs) have the capacity to overcome these barriers. This study aimed to investigate if the potential of these techniques, which has been reported in 2D, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 46 publications
1
48
0
Order By: Relevance
“…Child et al recently demonstrated, using a type I collagen gel culture system, an increased mNP (200 nm) uptake in the presence of a magnetic field, as well as a five-order magnitude increase in depth penetration. 17 Previous research has shown a size dependent NP response when a magnetic field was used, thus this study extends this work to investigate the most favorable mNP size in terms of uptake into a 3D tissue equivalent model, in order to optimize potential mNP use in a clinical situation.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…Child et al recently demonstrated, using a type I collagen gel culture system, an increased mNP (200 nm) uptake in the presence of a magnetic field, as well as a five-order magnitude increase in depth penetration. 17 Previous research has shown a size dependent NP response when a magnetic field was used, thus this study extends this work to investigate the most favorable mNP size in terms of uptake into a 3D tissue equivalent model, in order to optimize potential mNP use in a clinical situation.…”
Section: Introductionmentioning
confidence: 68%
“…Gels were prepared using the method previously developed by our group. 17 The following preparation method was used for making three gels. Quantities were increased depending on how many gels were required for each experiment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Different strategies have been postulated in order to overcome this limitation. Thus, the nanocarrier surface decoration with cell penetrating peptides (CPP) in combination with magnetic field guidance 7 and even the use of self-propelled devices have been described to achieve a higher penetration in 3D tissues. 8 A simpler approach consists in the local administration of proteolytic enzymes prior to the nanocarrier treatment, which has demonstrated a significant nanoparticle penetration enhancement within the tumoral tissue.…”
Section: Introductionmentioning
confidence: 99%